The enviromental effect on cooling rate of hot mix asphalt pavement - Mohd. Rosli Hainin, 1961-, author; Haryati Yaacob, author; Wardati Hashim, author (Skudai : Universiti Teknologi Malaysia, 2007)
PRZSL